Secondary malignancy risk following proton vs. X-ray radiotherapy of thymic epithelial tumors: a comparative modeling study of thoracic organ-specific cancer risk - König, Laila; Hörner-Rieber, Juliane; Forsthoefel, Matthew; Häring, Peter; Meixner, Eva; Eichkorn, Tanja; Krämer, Anna Sabrina; Mielke, Thomas; Tonndorf-Martini, Eric; Häfner, Matthias; Debus, Jürgen; Lischalk, Jonathan W. (Cancers, 2022)
Background: Proton beam radiotherapy (PBT) offers physical dose advantages that might reduce the risk for secondary malignancies (SM). The aim of the current study is to calculate the risk for SM after X-ray-based 3D conformal (3DCRT) radiotherapy, intensity-modulated radiotherapy (IMRT), and active pencil beam scanned proton therapy (PBS) in patients treated for thymic malignancies. Methods: Comparative treatment plans for each of the different treatment modalities were generated for 17 patients. The risk for radiation-induced SM was estimated using two distinct prediction models—the Dasu and the Schneider model. Results: The total and fatal SM risks estimated using the Dasu model demonstrated significant reductions with the use of PBS relative to both 3DCRT and IMRT for all independent thoracic organs analyzed with the exception of the thyroid gland (p ≤ 0.001). SM rates per 10,000 patients per year per Gy evaluated using the Schneider model also resulted in significant reductions with the use of PBS relative to 3DCRT and IMRT for the lungs, breasts, and esophagus (p ≤ 0.001). Conclusions: PBS achieved superior sparing of relevant OARs compared to 3DCRT and IMRT, leading to a lower risk for radiation-induced SM. PBS should therefore be considered in patients diagnosed with thymic malignancies, particularly young female patients.